Odoevsky's four pathways into modern fiction a comparative study - Cornwell, Neil (Manchester University Press : Distributed in the United States exclusively by Palgrave Macmillan, 2010)
This book takes four stories by the Russian romantic author Vladimir Odoevsky to illustrate 'pathways', developed further by subsequent writers, into modern fiction.